Porous Si@SiOx@N‐Rich Carbon Nanofibers as Anode in Lithium‐Ion Batteries under High Temperature. Issue 17 (29th August 2019) - Xia, Qi; Xu, Anding; Huang, Chuyun; Yan, Yurong; Wu, Songping
Abstract: A facile electrospinning technique followed by pre‐oxidation and carbonization treatment is adopted to synthesize silicon anode cladded with SiO x layer and N‐rich carbon nanofibers (Si@SiO x @NCNFs), in which post‐used polyacrylonitrile (PAN) yarn is chosen as single carbon source. As anode in Li‐ion batteries, elaborately designed Si@SiO x @NCNFs renders remarkable reversible capacities of 1045 mA h g −1 at the 500 th cycle under a current density of 8 A g −1 at 80°C, and 828 mA h g −1 after subsequent 500 cycles at 15 A g −1, mainly ascribed to the distinct hierarchical structure, N‐rich nature and enhanced pesudocapacitive behavior. When Si@SiO x @NCNFs is matched with commercial cathode LiFePO4, full cell delivers a stable capacity of 140 mA h g −1 at 100 mA g −1, accompanying with an energy density of 455 Wh kg −1 at 50 °C. These conspicuous features undoubtedly enable Si@SiO x @NCNFs to be promising anode materials for high‐power lithium‐ion battery used in harsh conditions. Abstract : Spinning a yarn : A facile electrospinning technique followed by heat treatment(pre‐oxidation and carbonization) is adopted to synthesize Si@SiO x @NCNFs, in which post‐used polyacrylonitrile yarn is chosen as single carbon source. As anode in Li‐ion batteries, elaborately designed Si@SiO x @NCNFs renders remarkable electrochemical performance, mainly ascribed to the distinct hierarchical structure, N‐rich nature, and enhanced pesudocapacitive behavior.